2010
DOI: 10.1246/cl.2010.1294
|View full text |Cite
|
Sign up to set email alerts
|

Self-generated Motion of Droplets Induced by Korteweg Force

Abstract: Phase-separating droplets exhibit self-generated motion depending on the composition of the constituent solution of a biocompatible material, aqueous two phase system. For higher concentrations than the equilibrium concentration, a droplet moved unidirectionally even in a homogeneous concentration field. For lower concentrations, the droplets hardly moved. The translational motion we observed is an effect of convection caused by Korteweg force.Chemical methods for controlling droplet motion provide the droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…Notwithstanding this transient, nonequilibrium character, the effective interfacial tension between miscible fluids plays a key role in a wide range of research fields of both academic and practical interest [19], from geosciences (e.g., in mantle convection, magma fragmentation, and the dynamics of Earth's core [20,21]) to hydrology [22], oil recovery [10], filtration and flow in porous media (e.g., in a chromatography column [23]), fluid removal [24], aquifer and soil remediation [25,26], and the modeling of hydrodynamic instabilities, e.g., in Rayleigh-Taylor [27] and Hele-Shaw [28,29] flows. Very recently, convection induced by Korteweg stresses has been proposed as a new mechanism for self-propulsion of droplets [30] and vesicles [31], demonstrating artificial chemotaxis and opening new scenarios in active matter and drug delivery systems. We may thus state quite generally that effective interfacial tension plays an important role in all miscible multifluid systems and at all length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding this transient, nonequilibrium character, the effective interfacial tension between miscible fluids plays a key role in a wide range of research fields of both academic and practical interest [19], from geosciences (e.g., in mantle convection, magma fragmentation, and the dynamics of Earth's core [20,21]) to hydrology [22], oil recovery [10], filtration and flow in porous media (e.g., in a chromatography column [23]), fluid removal [24], aquifer and soil remediation [25,26], and the modeling of hydrodynamic instabilities, e.g., in Rayleigh-Taylor [27] and Hele-Shaw [28,29] flows. Very recently, convection induced by Korteweg stresses has been proposed as a new mechanism for self-propulsion of droplets [30] and vesicles [31], demonstrating artificial chemotaxis and opening new scenarios in active matter and drug delivery systems. We may thus state quite generally that effective interfacial tension plays an important role in all miscible multifluid systems and at all length scales.…”
Section: Introductionmentioning
confidence: 99%
“…Emulsion droplets, in contrast, have the potential to be composed of bio-compatible liquids. It was also shown that emulsion droplets can self-propel by Marangoni stresses 10 that are maintained by chemical reactions 11 , micellar solubilization 12,13 , or liquid-liquid phase separations [14][15][16][17][18][19] . However, the realization of self-propelled Janus droplets has been proven difficult [20][21][22][23][24] in spite of the achievements obtained with emulsion droplets.…”
mentioning
confidence: 99%
“…Other studies were concerned with binary liquid mixtures featuring a two-phase region in their phase diagram. In [4,5] the binary system acetone-hexadecane and in [6,7] mixtures of aqueous solutions of poly-(ethylene glycol) (PEG) and sodium sulfate (Na 2 SO 4 ) were studied. However, the droplets driven by phase separation dynamics show only short active periods and their estimated cruising range is typically below 20 times their diameter.…”
mentioning
confidence: 99%